Pengaruh Hal Audit Utama, Kompleksitas Operasi, dan Komite Audit Terhadap Ketidaktepatan Waktu Pelaporan Audit - Hannah Paramita Freed; Christina Dwi Astuti; Mulyadi Siregar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of key audit matters, complexity operation and audit committee on audit report lag. The quantitative method used in this study uses secondary data sources in the form of annual reports and audited financial statements. The samples in this study consist of companies in the Properties & Real Estate industry which are listed on the Indonesia Stock Exchange (IDX), selected using the purposive sampling technique. The number of samples is 144 companies with 152 observations during the 2022–2023 period. Multiple linear regression analysis method was used as hypothesis testing in this study. The results of this study indicate that audit committee has a negative effect on audit report lag. Meanwhile, key audit matters and complexity operation have no effect on audit report lag.